Malignant Intracerebral Nerve Sheath Tumors: A Case Report with Review of the Literature - Faris Shweikeh; Doniel Drazin; Sergei I. Bannykh (Case Reports in Surgery)
The occurrence of benign nerve sheath tumors within the neuroaxis is uncommon. Even rarer is the finding within brain parenchyma, termed malignant intracerebral nerve sheath tumors (MINST). We present a case of MINST which occurred in the frontal lobe of an 18-year-old male that recurred almost 4 years later. Imaging demonstrated a 4.0 cm lesion with an associated mass effect. He underwent a right fronto-parietal craniotomy for gross total resection. Pathology was inconclusive with a Glioblastoma Multiforme (GBM) as the most likely diagnosis, though gliosarcoma and MINST were also highly considered. Postoperatively, he was treated with chemotherapy and radiation and followed for almost 4 years, when an MRI indicated a recurrence. Resection of the recurrence was highly suggestive of MINST. Surgery was followed by radiation and chemotherapy, but, less than 7 months later, he was readmitted for a surgical-site infection, and, after multiple surgeries, and his family terminated care. Recognizing this unusual tumor in the differential diagnosis of a heterogeneously enhancing intracerebral mass can help surgeons diagnose and treat it. This report also exhaustively reviews the literature and presents diagnostic and treatment strategies.